Muscular fatigue during 200 m front crawl - Figueiredo, P.; Pereira, S.; Goncalves, P.; Vilas-Boas, J. P.; Fernandes, R. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to evaluate muscle fatigue in upper and lower limbs as well as trunk muscles during a 200 m all-out front crawl effort. Surface electromyogram was collected from the flexor carpi radialis, biceps brachii, triceps brachii, pectoralis major, trapezius pars superior, rectus femoris, biceps femoris and tibialis anterior of 13 international level male swimmers. Velocity, stroke frequency and stroke length were calculated based on 3D video analysis. Spectral Indices of Muscle Fatigue (IMF) were calculated for each stroke of the each 25 m lap. During the 200 m, the rate of IMF changed against the first lap and increased gradually across successive laps, reflecting the evolvement of muscle fatigue for all studied muscles.